Searching for the ‘Middle Ground’: Non-native Chinese Language Teachers’ Cognition in the UK - Garombo, Chiara (2017)
In the last two decades, there has been broad research into the field of non-native speaker (NNS) teachers of English. Yet, even though in the UK, NNS Chinese teachers are raising in number and increasingly appreciated, there is still little published data investigating their backgrounds and cognitive level. Inspired by this gap and my experience as a student-teacher during my MA TCSOL, this current explorative-interpretative study explored the pathways and experiences leading to their cognitive processes with the aim of better understanding this underresearched group of professionals and of detecting the ‘middle ground’. More specifically, this study aimed to identify the pedagogical choices where East and West meet and learn from each other to overcome their shortcomings without losing their identity. By means of semi-structured multiple interviews through Skype, the present research examined the pathways and experiences of NNCSTs in the UK and the emerging beliefs which were found to be on four domains: their views on Chinese learners, on their role as CFL teachers, on foreign language teaching and on Chinese language teaching. On the whole, the findings showed balanced pedagogical approaches which allowed for the detection of the ‘middle ground’ at the cognitive level and stated classroom practice level. To deal with the complex cognitive domain of NNCSTs that emerged from this study, a focused training allowing for reflection on these blended cognitions is proposed, in addition to the need for further studies investigating NNCSTs actual classroom practice and the potential outcomes thereof. Lastly, this study supports a focus on collaboration between native and non-native CFL teachers to maximise the benefits of the intercultural awareness achieved by both.